Use of Microwave Radiometry to Monitor Thermal Denaturation of Albumin - Ivanov, Yuri; Kozlov, Andrey F.; Galiullin, Rafael A.; Tatur, Vadim Y.; Ziborov, Vadim S.; Ivanova, Nina D.; Pleshakova, Tatyana O.; Vesnin, Sergey G.; Goryanin, Igor (Frontiers in Physiology, 2018)
This study monitored thermal denaturation of albumin using microwave radiometry. Brightness Temperature, derived from Microwave Emission (BTME) of an aqueous solution of bovine serum albumin (0.1 mM) was monitored in the microwave frequency range 3.8 - 4.2 GHz during denaturation of this protein at a temperature of 56° C in a conical polypropylene cuvette. This method does not require fluorescent or radioactive labels. A microwave emission change of 1.5-2°C in the BTME of aqueous albumin solution was found during its denaturation, without a corresponding change in the water temperature. Radio thermometry makes it possible to monitor protein denaturation kinetics, and the resulting rate constant for albumin denaturation was 0.2 ± 0.1 min-1, which corresponds well to rate constants obtained by other methods.